Reproduction on Display: Black Maternal Mortality and the Newest Case for National Action - Cole, Haile Eshe (Journal of the Motherhood Initiative for Research and Community Involvement, 2018)
This essay critically examines the growing international attention given to Black maternal and infant health outcomes in the United States, and couches it within Black feminist theories of womanhood and motherhood. Existing Black feminist literature has acknowledged the ways in which Black women from the era of slavery have served as the embodiment of inhumanity and the calculating baton in which to measure against the personification of white virtue, womanhood, and motherhood. Moreover, these works have also significantly contributed to contextualizing and historicizing this problematic conception of the pathological Black mother. This piece highlights the ways in which current media depictions recreate problematic narratives of Black motherhood and uses the example of Black maternal mortality in the United States to 1) highlight the centrality of Black motherhood and reproduction within the narratives of Black pathology; 2) address the “spectacular” nature and fascination with Black suffering and death; and 3) underline the ways in which narratives around Black maternal and infant health align ideologically with normalized conceptualizations of the pathological Black body.